Optimalisasi Pariwisata Syariah Dalam Meningkatkan Sumber Daya Manusia Di Era Industri 4.0 - Murtadho, Fikri Ali (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
This research aims to analyze the optimization of sharia tourism in improving the quality of human resources (HR) in the industrial era 4.0. Sharia tourism, as part of the halal economy, has great potential to encourage economic growth and develop human resources that are globally competitive. The industrial era 4.0 is marked by advances in digital technology, which affects various sectors, including tourism. This research uses a qualitative approach with a literature study method to explore the relationship between the application of sharia principles in tourism and uses the SWOT analysis method to formulate strategies for improving sharia tourism and HR competencies, such as mastery of technology, service innovation and the integrity of Islamic values. The analysis results show that the application of digital technology, such as the Internet of Things (IoT), artificial intelligence (AI), and big data, in sharia tourism can increase operational efficiency while strengthening destination branding. Apart from that, human resource training based on technology and Islamic values ​​has been proven to be able to increase professionalism, productivity and the attractiveness of the sharia tourism sector. Thus, optimizing sharia tourism through technology integration and human resource development is a strategic step to face the challenges of the industrial era 4.0 and encourage inclusive and sustainable economic growth.